Pemanfaatan Sampah Plastik Sebagai Media Pembelajaran Mata Pelajaran Pendidikan Agama Islam Pada Siswa Kelas 1 di SDN 48 Gedongtataan Pesawaran - Komari, Komari; Nugroho, Anggi Septia; Putra, Arizal Eka (Widya Balina, 2023)
This research isrooted in the need for innovative approaches in the Islamic Religious Education learning process at the elementary level. The use of plastic waste/waste as a learning medium emerged as a response to two crucial issues: increasing students' learning ability and overcoming the problem of plastic waste. The research aims to evaluate the effectiveness of using waste/plastic waste media in increasing the comprehension ability of grade 1 students at SDN 48 Gedongtataan Pesawaran in Islamic Religious Education subjects. The research uses a classroom action research approach with one cycle. Data was obtained through classroom observations and Likert scales. Statistical and qualitative analyzes were used to interpret the results. During the observation, it showed that the majority of students had not achieved the expected development, indicating the need for more in-depth intervention in presenting the findings during the observation. Cycle I showed significant improvement, with a success percentage reaching 86%, exceeding the previously set target of 65%. This confirms that the use of plastic waste/waste media has a strong positive impact in increasing students' comprehension ability.